New genetic predictors for abacavir tolerance in HLA-B57:01 positive individuals - Pavlos, Rebecca; Deshpande, Pooja; Chopra, Abha; Leary, Shay; Strautins, Kaija; Nolan, David; Thorborn, Daren; Shaefer, Mark; Rauch, Andri; Dunn, David; Montaner, Julio; Rachlis, Anita; et al. (Human immunology, 2020)
Abacavir hypersensitivity syndrome (ABC HSS) is strongly associated with carriage of human leukocyte antigen (HLA)-B*57:01, which has a 100% negative predictive value for the development of ABC HSS. However, 45% of individuals who carry HLA-B*57:01 can tolerate ABC. We investigated immune and non-immune related genes in ABC HSS (n = 95) and ABC tolerant (n = 43) HLA-B*57:01 + patients to determine other factors required for the development of ABC HSS. Assignment of phenotype showed that ABC HSS subjects were significantly less likely than tolerants to carry only ERAP1 hypoactive trimming allotypes (p = 0.02). An altered self-peptide repertoire model by which abacavir activates T cells is in keeping with observation that endoplasmic reticulum aminopeptidase 1 (ERAP1) allotypes that favour efficient peptide trimming are more common in ABC HSS patients compared to patients who tolerate ABC. Independently, non-specific immune activation via soluble cluster of differentiation antigen 14 (sCD14) may also influence susceptibility to ABC HSS.